The anatomy of well-being: understanding its psychosocial and sociodemographic dimensions - Barros, Carlos; Malta Cruz, Mariana; Gaspar de Matos, Margarida (Frontiers in Sociology, 2025)
Migration processes should be analyzed in terms of their psychosocial impact within a multisystemic context. This study aims to identify the psychosocial and sociodemographic factors that influence the well-being of Portuguese migrants, focusing on aspects such as educational qualifications, health, employment status, the length of time they have been outside Portugal and where they live. Participants are 395 Portuguese emigrants currently living abroad, aged between 20 and 78 (M = 37.60, SD = 8.65). The participants live in various geographical locations. About three-quarters (77%, n = 302) of respondents lived in European countries, particularly in urban areas (71%, n = 281), mainly women (78%, n = 308). Linear regression models used as independent variables gender, health, marital status, qualifications, professional status, residence, age and years since emigrating and as dependent variables the satisfaction with social ties, connection, cohesion, acculturation and adaptation. Data were collected through an online survey using non-probabilistic recruitment, and analyzed with ANOVA for mean comparisons and stepwise linear regression to identify the strongest predictors of well-being dimensions. The results suggest that interventions aimed at promoting migrants' well-being should integrate the social, physical, and mental dimensions of health, recognizing the importance of support networks, a sense of belonging, employment conditions, and community cohesion for adaptation and integration. The study emphasizes the importance of synergy between individual and contextual well-being in creating healthy spaces, populations and communities.